Neuropathic pain: an updated grading system for research and clinical practice. Issue 8 (August 2016) - Finnerup, Nanna B.; Haroutounian, Simon; Kamerman, Peter; Baron, Ralf; Bennett, David L.H.; Bouhassira, Didier; Cruccu, Giorgio; Freeman, Roy; Hansson, Per; Nurmikko, Turo; Raja, Srinivasa N.; Rice, Andrew S.C.; et al.
Abstract : Abstract: The redefinition of neuropathic pain as "pain arising as a direct consequence of a lesion or disease affecting the somatosensory system, " which was suggested by the International Association for the Study of Pain (IASP) Special Interest Group on Neuropathic Pain (NeuPSIG) in 2008, has been widely accepted. In contrast, the proposed grading system of possible, probable, and definite neuropathic pain from 2008 has been used to a lesser extent. Here, we report a citation analysis of the original NeuPSIG grading paper of 2008, followed by an analysis of its use by an expert panel and recommendations for an improved grading system. As of February, 2015, 608 eligible articles in Scopus cited the paper, 414 of which cited the neuropathic pain definition. Of 220 clinical studies citing the paper, 56 had used the grading system. The percentage using the grading system increased from 5% in 2009 to 30% in 2014. Obstacles to a wider use of the grading system were identified, including (1) questions about the relative significance of confirmatory tests, (2) the role of screening tools, and (3) uncertainties about what is considered a neuroanatomically plausible pain distribution. Here, we present a revised grading system with an adjusted order, better reflecting clinical practice, improvements in the specifications, and a word of caution that even the "definite" level of neuropathic pain does not always indicate causality. In addition, we add a table illustrating the area of pain and sensory abnormalities in common neuropathic pain conditions and propose areas for further research.